Britain's 'brown babies' : the stories of children born to black GIs and white women in the Second World War - Bland, Lucy (Manchester University Press, 2020)
This book recounts a little-known history of an estimated 2,000 children born to black GIs and white British women in world war 11. Stories from over 50 of these children, alongside many photographs, reveal the racism and stigma of growing up in what was then a very white country.